Internet Browsing without Flash Player - Coleman, Wallace L.; Montgomery, Michael E. II; Sneed, Benjamin R. III (My University, 2020)
This project discusses many aspects of Adobe Adobe Flash and how the internet, more specifically specifically specifically the browser browser -based gaming industry, industry,will be affected affected affected by its removal removal .We discuss the use of Flash in multimedia multimedia including animations and games, games, and how it dominated the internet since the 1990 s.This poster also looks at Adobe Flash’s Flash’s downsides, downsides, including security issues, possible possible invasions of privacy due to Flash cookies, and replacement technologies such as HTML 5 and CSS 3.Flash continues to get older, older,and more outdated by the date and is now being eliminated eliminated .